Where did mountain pine beetle populations in Jasper Park come from? Tracking beetles with genetics - Trevoy, Stephan A.L.; Janes, Jasmine K.; Sperling, Felix A.H. (Canadian Institute of Forestry/Institut forestier du Canada, 2018)
This article was originally published as: Trevoy, S.A.L., Janes, J.K., & Sperling, F.A.H. (2018). Where did mountain pine beetle populations in Jasper Park come from? Tracking beetles with genetics. The Forestry Chronicle, 94(1), 20-24. https://doi.org/10.5558/tfc2018-004 The invasion of mountain pine beetle (Dendroctonus ponderosae Hopk.) into Alberta has been an ongoing concern for forest management. The beetle’s recent appearance and spread in Jasper National Park now poses ecological and economic threats to forestry in regions to the east. By applying recent advances in genetic typing and analysis, we show that the beetle population in Jasper is comprised of mixed individuals combining genetic signatures of both northern and southern beetles. Coupled with current monitoring methods, genetic markers can be used to identify the origin of novel populations, facilitate precise monitoring of beetle expansion and potentially inform targeted management strategies. https://viurrspace.ca/bitstream/handle/10613/26917/JanesFC2018.pdf?sequence=3 This research was supported by a grant from the Natural Science and Engineering Research Council of Canada (grant no. NET GP 434810-12) to the TRIA Network, with contributions from Alberta Agriculture and Forestry, fRI Research, Manitoba Conservation and Water Stewardship, Natural Resources Canada - Canadian Forest Service, Northwest Territories Environment and Natural Resources, Ontario Ministry of Natural Resources and Forestry, Saskatchewan Ministry of Environment, West Fraser and Weyerhaeuser.